Using parent report for assessment of the first language of English language learners - May, A.; Williams, Cori (Speech Pathology Australia, 2012)
Assessment of both languages is recommended when assessing English language learners (ELL) but may not always be practical. Use of a parent questionnaire, such as the Alberta Language and Development Questionnaire (ALDeQ), can assist in obtaining first language (L1) information. This study aimed to use the Canadian developed ALDeQ within an Australian population and determine whether ALDeQ scores would differentiate between ELL who were typically developing compared to ELL with language difficulty. A background questionnaire and the ALDeQ were administered to parents of 14 ELL that were typically developing and 3 ELL with apparent language difficulty aged between 5;3 and 8;7 years. ALDeQ Total Scores of typically developing Australian ELL were consistent with the Canadian norming population and significantly higher than the scores of the group with language difficulties. Although results are promising, further research is necessary to support use of the ALDeQ to investigate L1 abilities of ELL within an Australian population.